2011
DOI: 10.1016/j.ijid.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis in childhood: a retrospective study of 650 hospitalized pediatric patients

Abstract: Gastroenteritis is a common reason for hospital admission in previously healthy children during the first years of life. Rotaviruses were found to be the most common pathogens in our cohort. On the basis of clinical and laboratory parameters it appears possible to distinguish between the different causative agents. This may have implications for hospital hygiene management and for the identification of predictive markers of a severe course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
72
2
30

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 23 publications
(25 reference statements)
14
72
2
30
Order By: Relevance
“…Diarrheic diseases, although presenting lower and more stable percentages, are still an important public health problem. Studies have shown that cases of acute, serious diarrhea persist and are associated with one-third of childhood hospitalizations and an estimated 600,000 deaths per year in children worldwide 3,8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diarrheic diseases, although presenting lower and more stable percentages, are still an important public health problem. Studies have shown that cases of acute, serious diarrhea persist and are associated with one-third of childhood hospitalizations and an estimated 600,000 deaths per year in children worldwide 3,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…In medium and low-income countries, infectious diseases are still important causes of hospitalization, despite the decline in hospitalizations from acute diarrhea since the advent of oral rehydration therapy and such interventions as maternal breastfeeding and immunizations 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory symptoms and systemic inflammation parameters differed between the different pathogens. (12) A study comparing the proportion of hospitalizations for diarrhea attributable to rotavirus found increased hospitalization rates in recent years, 21% between 1986 and 1999, 39% between 2000 and 2004, both in developed and developing countries. (13) After this period, there was a reduction in hospitalization rates compared to other causes of diarrhea, suggesting the importance of oral human rotavirus vaccine in reducing hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda, tüm gaita örneklerinin % 13'ünde viral antijen tespit edilmiştir. Bu değer, literature bakıldığında değişik yayın-larda % 31.5-% 59 arasında değişmekte-dir (8,24,25) . Bu farkın özellikle, çalışmanın yapıldığı gruplardaki hasta sayısından ve aşılama oranlarından kaynaklandığını düşünmekteyiz.…”
Section: Bulgularunclassified